Flood victims' preferences towards takaful flood coverage: an analysis based on structural equation modelling - Che Mohd Salleh, Marhanum; Abdullah, Nurdianawati Irwani (IIUM Press, International Islamic University Malaysia, 2018)
This article examines the preferences of flood victims in Malaysia for future participation in the Takaful scheme. A quantitative methodology is adopted in this research where survey have been conducted among 349 flood victims in east coast area (Kelantan, Terengganu, and Pahang) of Malaysia. Based on structural equation modelling analysis, it is found that the factors that have significantly influenced the victims to participate in the Takaful scheme if given opportunity in future are their awareness on the scheme and because of financial difficulties caused by flood. In addition, at least 50 percent of the victims have experienced final losses not more than RM10,000. Moreover, it is found that majority of them were preferred to pay monthly Takaful contribution less than RM100. Results of this research urge the industry players to strategise their marketing effort by increasing awareness among the rural population towards financial preparation for disasters as well as structuring micro Takaful scheme to capture the low-income group.